Driving the quadricyclane-to-norbornadiene isomerization by charge separation with perylenediimide as electron acceptor - Zika, Wiebke; Leng, Andreas; Weiß, René; Pinter, Simone; Schüßlbauer, Christoph; Clark, Timothy; Hirsch, Andreas; Guldi, Dirk Michael (Chemical Science, 2023)
Through comprehensive photo-assays, this study investigates the reaction coordinate governing the interconversion between quadricyclane (QC) and norbornadiene (NBD) upon photo-irradiation up to a wavelength of 550 nm. To harness this spectroscopic range for energy release, we link the NBD-core with a highly electron-accepting perylenediimide (PDI) with broad absorption, achieving strong electronic coupling between them. We detail the successful synthesis and present extensive DFT calculations to determine the amount of stored energy. By means of transient absorption spectroscopy, an oxidative electron transfer is observed during the QC-to-NBD isomerization following the initial PDI photoexcitation. This charge-separated state is key to triggering the back-isomerization with visible light excitation.
CRIS-Team Scopus Importer:2023-10-20